Penggunaan Model Pembelajaran Pendidikan Karakter Abad 21 pada Anak Usia Dini - Yenni Fitra Surya (LPPM Universitas Pahlawan Tuanku Tambusai, 2017)
Absolute character education was undertaken in the 21st century in early childhood as curative measures and social pathology in the community, but a preventive measure to the formation the good character of each student have not effectively used in character education. In addition to cognitive learning students' character formation should be noted. In fact, often the formation of character early on is often forgotten. The aim of research explained comprehensively the nature of character education in the 21st century in childhood, explained comprehensively the use of models of learning in character education in the 21st century in childhood, explained comprehensively use learning approaches in character education in the 21st century to children aged early. The research method used in this study is a literature review is to connect research with the existing literature and fills the gaps in previous research. The results obtained in this study the use of the learning model of character education in the 21st century in childhood is the process of empowering the learner process of humanization (humanizing), and the process of acculturation, learning models of education namely learning model planting value, based on the development of moral reasoning, value analysis, and project citizen, effective use helps learners develop competencies become good citizens